A BRIEF PSYCHO-EDUCATION INTERVENTION FOR PATIENTS WITH NON-EPILEPTIC ATTACK DISORDER (NEAD). Issue 9 (13th August 2015) - Wiseman, H; Brown, R; House, A; Howlett, S; Reuber, M
Abstract : Objective: We describe the roll-out of a brief psycho-education intervention for individuals with non-Epileptic Attack Disorder (NEAD), which has been developed for healthcare professionals with limited experience in delivering psychological treatments. Method: The psycho-education package is comprised of four one-to-one sessions. The first session provides an explanation of the NEAD diagnosis and introduces the patient to idea that mind and body are linked. The second session teaches behavioural strategies for controlling seizures, including sensory grounding, relaxation and imagery. The third session focuses on identifying and reducing avoidance behaviours that may have been adopted due to seizure symptoms. The final session focuses on values and going forward. Eighteen nurses and therapists attended a training to deliver this package. The two day training intervention included lectures and interactive workshops with actors. The initial roll out stage involved fourteen NHS trusts across the country. Ten months following training, therapists were asked to complete a survey to assess the extent they used this intervention and that they found it to be relevant, comprehensive, and sufficient. Patients with NEAD who attended for psycho-education were also asked to complete pre and post questionnaires including the following measures; Work and Social Adjustment scale (WSAS), Brief Illness Perception Questionnaire (Brief IPQ), Clinical outcomes in routine evaluation (CORE) and the EuroQoL-5D3L and NewQOL quality of life measures. Results: Since the training, the package has been delivered in four centres. Recruitment and data collection are ongoing. Preliminary analysis of the pre and post participant data shows that following intervention, participants viewed their seizures as significantly less threatening (IPQ, p=0.002), and reported significantly less distress (CORE, p=0.01) The collection of therapist feedback about the use of the intervention is ongoing. Conclusion: It is feasible for healthcare professionals with minimal training in psychological intervention to deliver a brief psycho-education package for individuals with NEAD. Further analysis is needed to understand the full effectiveness of this intervention but preliminary results show that this intervention may have positive effects on the way individuals view their seizures and on their overall wellbeing.